Suurimpien yritysten rooli Suomen kansantaloudessa - Jyrki Ali-Yrkkö; Ilkka Ylhäinen; Mika Pajarinen; Tero Kuusi (The Research Institute of the Finnish Economy (ETLA), 2021)
– In this study, we have analysed the role of the largest companies in the Finnish economy. According to the results, the list of ten largest companies in terms of their domestic value added is diverse and includes companies operating in the manufacturing industry, the service industry, as well as the financial industry. In 2019, these top 10 companies together produced 5.7% of the Finnish gross domestic product (GDP). In terms of domestic employment, the significance of this group remains lower, accounting for 3.7% of the employment of the business sector. Although both the share of GDP and employment have declined, the role of these top 10 companies in the Finnish economy remains significant.
Keywords: F23; L25; E22; M21; L11; 330; Large; Largest; Companies; Firms; GDP; Gross domestic product; Concentration; Group; Granular